Towards a performance-oriented management for large-scale irrigation systems: case study, Rahad scheme, Sudan - Hamid, S.H.; Mohamed, A.A.; Mohamed, Yasir Abbas (Wiley, 2011)
The underperformance problem of large-scale irrigation systems particularly in developing countries, has adversely affected levels of production of those systems. The fact that these irrigation systems are not managed in response to their performance has been identified as the main reason behind their malfunctioning. A performance-oriented management approach is demonstrated here to help irrigation system managers take the right decisions, through continuous in-season performance assessment. The Advanced Very High Resolution Radiometer satellite images of the National Oceanic and Atmospheric Administration (NOAA-AVHRR) for the year 2000, complemented by water release data, were used to assess the performance of the Rahad irrigation scheme, Sudan (126 000 ha), on a 10-day time step. The Surface Energy Balance Algorithm (SEBAL) was used to process the NOAA-AVHRR images. The decisions on irrigation water allocation are guided by maps of the relative water supply and soil moisture content generated for the last time step. Further decision support could be realized using the performance indicators of the system and the soil water balance for the given time step. A semiautomatic computer program was developed which can be easily used by field staff to support their management decisions. It is anticipated that the application of such an approach will improve the performance of large-scale irrigation systems, and support development of a performance-oriented management culture among the staff of these irrigation systems.